2008
DOI: 10.1002/aur.2
|View full text |Cite
|
Sign up to set email alerts
|

The potential role for emergence in autism

Abstract: Although most research on autistic behavior has considered autism categorically, the increasingly apparent genetic and phenotypic complexities of autism are prompting a more dimensional approach to this area. The long-standing interest in a less categorical approach is made clear from a review of literature. The accumulating empirical support for viewing autism-related phenomena as separable and fractionable is outlined and includes data indicating that many of the behaviors occur in isolation in family member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 170 publications
(164 reference statements)
3
29
0
Order By: Relevance
“…Recent studies have shown a continuous distribution of autistic behavioural features in families of probands and in the general population (Constantino and Todd 2003;Spiker et al 2002), the genetic separability of the primary diagnostic components , genetic heterogeneity (Anderson 2008;Cook 1998; The Autism Genome Consortium 2007) and the likely effect of environmental factors (Herbert et al 2006). These findings have led to an increasing perception of autism as a heterogeneous condition (Anderson 2008;Happé et al 2006, Spiker et al 2002).…”
Section: Perception Of Autism As a Unitary Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown a continuous distribution of autistic behavioural features in families of probands and in the general population (Constantino and Todd 2003;Spiker et al 2002), the genetic separability of the primary diagnostic components , genetic heterogeneity (Anderson 2008;Cook 1998; The Autism Genome Consortium 2007) and the likely effect of environmental factors (Herbert et al 2006). These findings have led to an increasing perception of autism as a heterogeneous condition (Anderson 2008;Happé et al 2006, Spiker et al 2002).…”
Section: Perception Of Autism As a Unitary Conditionmentioning
confidence: 99%
“…These findings have led to an increasing perception of autism as a heterogeneous condition (Anderson 2008;Happé et al 2006, Spiker et al 2002). Yet despite an explicit awareness of heterogeneity issues over many years (Anderson 2008) the research designs of many empirical studies treat autism as a unitary condition .…”
Section: Perception Of Autism As a Unitary Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research regarding distinctive but related neurodevelopmental disorders such as attention deficit hyperactivity disorder (AD/HD) and autism, 1 is increasingly moving towards determining cognitive endophenotypes that can characterize the heterogenic nature of these disorders, instead of trying to pinpoint which single cognitive construct underlies all AD/HD or autism characteristics (e.g., Anderson, 2008;Castellanos & Tannock, 2002;Happe´, Ronald & Plomin, 2006;Viding & Blakemore, 2007). These endophenotypes can be conceptualized on a neurophysiological, neuroanatomical and/or cognitive level, and they are the intermediate between the behavioural classification (i.e., AD/HD as phenotype) and the biological variables (i.e., genotypes and environment) that cause the disorder (Gottesman & Gould, 2003).…”
mentioning
confidence: 99%
“…Recent research has focused on the role of synapse structure and signaling pathways in the brain as central to the development of ASD. Anderson [180] suggests in his review that the novel, "emergent" phenomena may arise in the individual from interacting of underlying genetic and biological factors or cooccurring traits.…”
Section: Resultsmentioning
confidence: 99%